2005
DOI: 10.1016/j.ydbio.2005.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Expression of epithin in mouse preimplantation development: Its functional role in compaction

Abstract: The preimplantation development of mammalian embryo after fertilization encompasses a series of events including cleavage, compaction, and differentiation into blastocyst. These events are likely to be associated with substantial changes in embryonic gene expression. In the present study, we explored the expression patterns and function of epithin, a mouse type II transmembrane serine protease, during preimplantation embryo development. RT-PCR analysis showed that epithin mRNAs were detectable during the cleav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…RNA interference (RNAi) is an established powerful experimental tool for analyzing gene function in mammalian cells and embryos [14][15][16][17]. Applying a similar approach, we used an siRNA strategy to explore the specific function of the SCF/cKit system in mouse pre-implantation embryonic development.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…RNA interference (RNAi) is an established powerful experimental tool for analyzing gene function in mammalian cells and embryos [14][15][16][17]. Applying a similar approach, we used an siRNA strategy to explore the specific function of the SCF/cKit system in mouse pre-implantation embryonic development.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…-dependent Ecadherin-catenin complex (Vestweber and Kemler 1985;Johnson et al 1986) but also through the co-localising vezatin adhesion complex (Hyenne et al 2005), the Ca 2+ -independent immunoglobulin family nectin complex ) and the epithin membrane serine protease (Khang et al 2005). Close cell-cell adhesion at compaction is accompanied by restructuring of the membrane cytoskeleton involving nucleation and formation of actin filaments (Sun et al 2013) facilitated by the suppression in expression of the actin filament depolymerising protein, cofilin-1 (Ma et al 2009).…”
Section: +mentioning
confidence: 99%
“…At this stage the cells establish gap junctions [10,11]. Compaction is mediated by E-cadherin and associated proteins [12][13][14][15][16][17]. A detailed description of the mechanisms driving compaction is tangential to this review but can be found in Chen et al [18].…”
Section: Forming Trophectodermmentioning
confidence: 99%